Pengembangan Instrumen Penelitian Mengenai Perilaku SMA/ MA Terhadap Pencemaran Air - Chetty Agnina Raharjo; Febrianawati Yusup (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
This study aims to develop a valid and reliable instrument and can be used to measure the behavior of high school students regarding water pollution. The steps undertaken to develop this instrument are the development of a collection of question items, validation of a collection of question items, taking opinion experts, trials, instrument administration, documentation, calculating the validity and reliability of instruments using trials of this instrument which contains the habits of water pollution. The validation stage was submitted to one high school biology teacher and two biology lecturers. The instrument test was conducted with a group of 20 high school students with 15 questions. The results showed that the Corrected Item-Total Correlation of 15 questions created and validated there were 6 questions that were positive while 9 other questions were negative. Then for the value of Reliability Statistics for Cronbach's Alpha is 0.469 and Cronbach's Alpha Based on Standardized Items is 0.417. The conclusions from the results of the study as a whole assessment instruments are good and can be used.Keywords: Behavior, Water Pollution, Instrument Development.